2018
DOI: 10.1111/cpr.12474
|View full text |Cite
|
Sign up to set email alerts
|

Roflumilast enhances cisplatin‐sensitivity and reverses cisplatin‐resistance of ovarian cancer cells via cAMP/PKA/CREB‐FtMt signalling axis

Abstract: Roflumilast enhanced DDP sensitivity and reversed the DDP resistance of ovarian cancer cells via activation of cAMP/PKA/CREB pathway and upregulation of the downstream FtMt expression, which has great promise in clinical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…As a broad-spectrum chemotherapeutic drug, the application of cisplatin in glioma treatment is still unsatisfactory. Considerable evidence showed that novel chemosensitizers could effectively improve the anticancer effects of cisplatin and reduce the undesirable adverse effects (Zhang et al 2014;Gong et al 2018;Wandee et al 2019;Zhou et al 2019). Recently, researchers have focussed on the synergistic properties of NB that can effectively improve cell permeability, open BBB, and accelerate drug distribution in tumour tissue (Cai et al 2008;Duan et al 2016;Xing et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a broad-spectrum chemotherapeutic drug, the application of cisplatin in glioma treatment is still unsatisfactory. Considerable evidence showed that novel chemosensitizers could effectively improve the anticancer effects of cisplatin and reduce the undesirable adverse effects (Zhang et al 2014;Gong et al 2018;Wandee et al 2019;Zhou et al 2019). Recently, researchers have focussed on the synergistic properties of NB that can effectively improve cell permeability, open BBB, and accelerate drug distribution in tumour tissue (Cai et al 2008;Duan et al 2016;Xing et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Cisplatin, a traditional chemotherapeutic drug, has been widely applied in treating human solid malignancies, including nasopharyngeal, oesophageal, and lung carcinoma, ovarian cancer, and glioma (Rocha et al 2015;Gong et al 2018;Okamoto et al 2018). Cisplatin can interact with DNA and activate apoptotic signalling transduction, which is also negatively regulated by prosurvival factors, such as Bcl-2 family members, PI3K/Akt, and various drug efflux pumps (e.g., ABCB1, also named P-gp or MDR1) (Wijdeven et al 2016;Lipinska et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CREB can regulate transcription of various other transcription factors as well as genes that regulate metabolism, the cell cycle and secretion . Therefore, dysfunction of the cAMP‐dependent pathway can contribute to tumor development, tumor progression and also development of anticancer drug resistance . GPRC5A is known to contain a binding site for CREB in the 5′ promotor region.…”
Section: Discussionmentioning
confidence: 99%
“…37 Therefore, dysfunction of the cAMPdependent pathway can contribute to tumor development, tumor progression and also development of anticancer drug resistance 38 . 39 GPRC5A is known to contain a binding site for CREB in the 5 0 promotor region. Therefore, GPRC5A may form a negative feedback loop in which the phosphorylation of CREB is suppressed.…”
Section: Discussionmentioning
confidence: 99%